2016
DOI: 10.18632/oncotarget.8914
|View full text |Cite
|
Sign up to set email alerts
|

Interference with mutagenic aflatoxin B1-induced checkpoints through antagonistic action of ochratoxin A in intestinal cancer cells: a molecular explanation on potential risk of crosstalk between carcinogens

Abstract: Foodborne aflatoxin B1 (AFB1) and ochratoxin A (OTA) cause genotoxic injury and subsequent tumor formation. As a biomarker of oncogenic stimulation by genotoxic mycotoxins, p53-triggered Mdm2 was assessed in intestinal cancer cells. AFB1 increased Mdm2 reporter expression in a dose-dependent manner. However, this was strongly antagonized by OTA treatment. As a positive transcription factor of Mdm2 expression, p53 levels were also increased by AFB1 alone and reduced by OTA. With marginal cell death responses, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Prolonged storage of the chicken's feed creates a high synthesis of the aflatoxin (Sarma et al, 2017). Aflatoxin induces severe cellular defects and carcinogenesis (Kim et al, 2016). The disease is caused by aflatoxin known as aflatoxicosis (Wogan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged storage of the chicken's feed creates a high synthesis of the aflatoxin (Sarma et al, 2017). Aflatoxin induces severe cellular defects and carcinogenesis (Kim et al, 2016). The disease is caused by aflatoxin known as aflatoxicosis (Wogan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the above‐mentioned subtractive technologies, additive manufacturing techniques (inkjet, screen, and 3D printing) offer extremely low cost, completely digital, and highly scalable manufacturing processes . Due to these advantages, additive manufacturing techniques have been used to realize sensors, transistors, RF inductors, RF capacitors, RF filters, RF identification (RFID) tags, and so on. There have only been a few reports on printed RF switches .…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that AFB 1 is harmful to the liver and kidneys of mammals and that it is regarded as a representative orally ingested carcinogen [10]. However, accumulating evidence has indicated that AFB 1 is immunotoxic to mammals [11,12]; these results showed that low-level AFB 1 (≤ 0.025 mg/kg) exposure significantly increased the expression of proinflammatory cytokines, such as interferon-γ (IFN-γ) and tumor necrosis factor-alpha (TNF-α), by T cells and NK cells in rats, although high-level AFB 1 (0.4 to 0.8 mg/kg) exposure significantly decreased both the lymphocyte response to mitogens and macrophage migration in pigs.…”
Section: Introductionmentioning
confidence: 99%